Regulating Halal Products in Indonesia: Between Religious Needs and Socio-Economic Challenges (Mazahib, 2019)
As the most populous Muslim country in the world, Indonesia needs to spend seven decades until finally enacted the Halal Product Assurance Law in 2014.  There are mixed responses in welcoming this law.  Many Muslims are incredibly pleased with this law, while others believe that this law would create social and economic problems, instead. Four years have lapsed and the law is still difficult to be implemented, since the state has produced none of the implementing regulations of the said law.  Meanwhile, the National Agency for Halal Product Assurance is newly established in 2018.  Therefore, the law on halal product assurance is really at stake.  It seems that the state enacted it half-heartedly. This paper discusses the dynamic of regulating halal products in Indonesia, between spiritual needs and socio-economic challenges. Less Muslim argued that halal is not part of Islamic teaching, yet many people believe that halal product in Indonesia is not merely a religious issue but also a social, economic and even political issue.  The methods for this research are both normative and qualitative. Data are collected mainly through documents, library materials, and field research. To sharpen the findings, comparative studies with Malaysia and Thailand were conducted. In the end, this research reveals the socio-economic dynamics of halal product regulation in Indonesia amid which is beyond religious issues.Keywords:  halal product, Indonesia, regulation.